(untitled) (KYAMC Journal, 2022)
Background: Urethral stricture is a chronic and common urological problem in Bangladesh and its management poses a big challenge to urologists. Surgical treatment of urethral stricture diseases is a continuously evolving process, and the superiority of one technique over another has yet to be clearly demonstrated. Urethrotomy is the most commonly used technique but long term results are not satisfactory. Long penile urethral strictures are best treated by substitution urethroplasty. The ideal graft material for substitution urethroplasty is constantly evolving. Buccal mucosa produces excellent result but is associated with many long term donor site complications. Lingual mucosa is an alternative donor site for graft urethroplasty and achieved good functional and aesthetic results. Materials & Methods: A hospital based prospective study was conducted in the department of urology, Dhaka Medical College Hospital from July 2016 to March 2017. Total 40 patients were included in this study. They were divided in two groups, group 1 was treated by lingual mucosal graft and group 2 was treated by buccal mucosal graft. All patients were followed up for six months noting pre and post-operative maximum urine flow rate (Qmax), voiding time and complications at both urethroplasty and donor site. Results: There were no significant differences in overall operative success rate between two groups of patients. But complications at donor site were higher in group 2 patients. Conclusion: Lingual mucosal graft urethroplasty may be preferred to buccal mucosa in anterior urethral stricture as it is easy to harvest and is associated with less short and long term donor site complications without significant difference in operative success rate. KYAMC Journal Vol. 13, No. 02, July 2022: 108-114